Revisão taxonômica de Schizolecis Britski & Garavello, 1984 : (Loricariidae: Hypoptopomatinae) - Kusma, Camila Munareto (2013)
The genus monotypical Schizolecis was proposed by Britski & Garavello (1984), being Microlepidogaster guntheri Miranda Ribeiro, 1918 the type species. Its distribution occurs from the north of the state of Santa Catarina until the north of the state of Rio de Janeiro, Brazil, comprising several coastal river basins. Due to the act that the genus is widely distributed in such isolated river basins, it was suggested the possibility of more than one species being included in what today we know as Schizolecis guntheri. To test this hypothesis, the following morphometric analysis were performed: tradition biometry and comparision of the interval of proportions; multivariate analyses of Principal Components and Canonical Variables and multivariate analyses of geometric morphometry using Relative Warps. Perceptible differences were not found among the individuals of the populations analyzed of Schizolecis guntheri, being only detected a gender dimorphism among the samples from Baía da Ilha Grande, in the state of Rio de Janeiro. A taxonomic revision was performed, together with a redescription of the genus and species. According to the results, it is concluded that all populations in differents coastal river basins of the state of Santa Catarina until the state of Rio de Janeiro, are a single species Schizolecis guntheri.